Dinamika Konflik antar Wahabi dan Aswaja di Aceh - Chairun Nisak, Cut Lusi; Rohmah, Tuthi’ Mazidar (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This article aims to discuss the dynamics of the conflict between Aswaja and Wahabi ideologies in Aceh, utilizing a literature review approach. The data for this article were obtained from relevant literature sources, including books and scholarly journals. The study reveals that religious conflicts in Aceh have occurred in various historical periods. These conflicts involve differing perspectives and have resulted in tensions among groups in Aceh, including the rejection of religious figures, the dissolution of religious gatherings, and debates on religious practices. The conflicts are closely related to the social and political context of Aceh, as well as the differing interpretations of religion between the exclusive Wahabi ideology and the inclusive Aswaja ideology. Aswaja, following the Shafi'i school of thought, has a distinct cultural emphasis on celebrating religious traditions, while Wahabi ideology opposes such practices and considers those who do not adhere to their ideology as infidels. In summary, the conflicts are driven by divergent views on religious practices, interpretations of religion, and beliefs in the existence of God. Abstrak Artikel ini bertujuan untuk mendiskusikan tentang dinamika konflik antara paham aswaja dan wahabi di Aceh dengan menggunakan pendekatan kajian literatur. Data dalam artikel ini diperoleh dari literatur-literatur berupa buku dan jurnal ilmiah yang relevan. Kajian ini menunjukkan dinamika konflik keagamaan di Aceh telah terjadi dalam beberapa periode sejarah. Konflik ini melibatkan perbedaan pandangan dan telah menyebabkan ketegangan antar kelompok di Aceh yang mencakup penolakan terhadap tokoh agama, pembubaran pengajian, dan perdebatan tentang praktik keagamaan. Konflik ini terkait dengan konteks sosial dan politik Aceh, serta perbedaan interpretasi agama antara paham Wahabi yang eksklusif dan paham Aswaja yang inklusif. Paham Aswaja, yang mengikuti mazhab Syafi'i, memiliki budaya yang berbeda dengan paham Wahabi. Aswaja menekankan nilai-nilai budaya seperti merayakan tradisi keagamaan, sementara Wahabi menentang praktik-praktik tersebut dan mengkafirkan mereka yang tidak sejalan dengan paham mereka.